An assessment of factors influencing technician turnover rates in agriculture - Schiess, Ryan (Kansas State University, 2022)
Agriculture Producers all around the world rely on technicians to diagnose and repair their equipment. Long after the sale, technicians are working with customers to keep their equipment investment operating as it should. Technicians are, therefore, crucial to SmartAg and vital to their long run success. Figuring out how to attract and retain good technicians is a critical strategic imperative for dealership organizations and for their supplier companies. This study focused on improving understanding about the factors that determined the retention of technicians at farm equipment dealerships. It is an important study because although retention has been studied extensively in many industries, it has not received particular attention in the agricultural equipment industry. Where it has been studied in the industry, the focus has not been on service technicians. The study used data from 87 sample dealerships of a major multinational manufacturer distributed across the United States. The data covered technician related factors over the last 12 months of dealership operations. Although turnover is normal in any business and in the economy, the study’s results showed that the number of technicians quitting exceed the number being hired during August through November. From December through July, the dealerships hired more technicians than lost them. In the United States, demand for technical services increase during August through November when producers are harvesting their crops. This cycle of events suggests a need to reduce the pressure the dealerships experience when they have technician deficits. The study shows that technician retention is positively influenced by training. As well as Smart Tech Assistance Center Score (STACS), a measure of how well technicians completed their case when seeking assistance from SmartAg, and parts and training credit goal achievement scores, which measure the dealerships’ actual to planned training credit hours, all increase retention with statistically significant coefficients. Additionally, increasing average labor efficiency, which is also influenced by training, also reduces technician turnover. Although salaries and other financial compensations were not considered in this work because they have been shown to have a mixed impact on retention across many industries, this study directs dealerships’ attention to enhancing the capacity of their technicians to do their work. And it would seem that by equipping them with the knowledge to do their work, they feel a higher level of commitment and loyalty to their employer, encouraging them to stay longer.
Keywords: Employee retention; Ag tech; Farm equipment; Agribusiness